Fricke and polymer gel 2D dosimetry validation using Monte Carlo simulation - Vedelago, José Alberto (2016)
Complexity in modern radiotherapy treatments demands advanced dosimetry systems for quality control. These systems must have several characteristics, such as high spatial resolution, tissue equivalence, three-dimensional resolution, and dose-integrating capabilities. In this scenario, gel dosimetry has proved to be a very promising option for quality assurance. In this study, the feasibility of Fricke and polymer gel dosimeters suitably shaped in form of thin layers and optically analyzed by visible light transmission imaging has been investigated for quality assurance in external radiotherapy. Dosimeter irradiation was carried out with a 6-MV photon beam (CLINAC 600C). The analysis of the irradiated dosimeters was done using two-dimensional optical transmission images. These dosimeters were compared with a treatment plan system using Monte Carlo simulations as a reference by means of a gamma test with parameters of 1 mm and 2%. Results show very good agreement between the different dosimetric systems: in the worst-case scenario, 98% of the analyzed points meet the test quality requirements. Therefore, gel dosimetry may be considered as a potential tool for the validation of other dosimetric systems.